2016
DOI: 10.1016/j.ceramint.2016.03.101
|View full text |Cite
|
Sign up to set email alerts
|

A study of the oxidation behavior of CrN and CrZrN ceramic thin films prepared in a magnetron sputtering system

Abstract: CrN and CrZrN ceramic thin films were produced by a planar type reactive sputtering system on glass and stainless steel substrates. We investigated oxidation resistance of CrN and CrZrN ceramic thin films with different Zr contents. The structure of the films at different thermalannealing temperatures was investigated by X-ray diffraction (XRD), atomic force microscopy (AFM) and scanning electron microscopy (SEM). The mechanical properties of the films at different thermal-annealing temperatures were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The deposited hard film, as the name implies, must have a higher value of mechanical properties such as hardness, wear resistance and tribological properties. The mechanical, wear and tribological properties of the film are affected by the phases and orientations of the films as reported in the literature [38,44]. So the study of the preferred orientation of the CrN thin films is also important from an application point of view.…”
Section: Effect Of Substrate Materials (In Terms Of Xrd and Surface Amentioning
confidence: 94%
“…The deposited hard film, as the name implies, must have a higher value of mechanical properties such as hardness, wear resistance and tribological properties. The mechanical, wear and tribological properties of the film are affected by the phases and orientations of the films as reported in the literature [38,44]. So the study of the preferred orientation of the CrN thin films is also important from an application point of view.…”
Section: Effect Of Substrate Materials (In Terms Of Xrd and Surface Amentioning
confidence: 94%
“…Among the existing options for a third chemical element, zirconium addition shows great promise, seeing that this element has been used in other systems. KHAMSEH e ARAGHI [20] reported the increase of oxidation temperature from 873 K to 1073 K for CrZrN (0.4 at.%) thin films while maintaining an elevated hardness.…”
Section: Introductionmentioning
confidence: 99%
“…However, further research has been devoted to the development of ternary systems to meet the harsh criteria of a fastchanging industry. Especially in an attempt to improve the hardness, friction resistance, and oxidation-resistance of CrN, the incorporation of elements such as Zr, Al, or Si into a Cr-N coating has been actively introduced [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the Cr-based ternary transition-metal nitrides, CrZrN coatings provide quite unique characteristics relative to CrN [4,6,8,9]. Kim et al [4] reported that the maximum hardness of CrZrN with an increase of up to 12.1 at.% of Zr content reached 34 GPa, as well as the tribological properties from the ball-on-disc wear test, which revealed no film failure compared to CrN.…”
Section: Introductionmentioning
confidence: 99%